Team Players - Lupica, Mike (New York : Simon & Schuster Books for Young Readers, 2018)
"A girl with Asperger's joins Cassie's softball team but not everyone on the team welcomes her, creating a rift between Cassie and her teammates"--
Keywords: Softball players -- Juvenile fiction; Softball teams -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Asperger's syndrome -- Juvenile fiction; Autism -- Juvenile fiction; Softball players -- Fiction; Softball teams -- Fiction; Interpersonal relations -- Fiction; Friendship -- Fiction; Asperger's syndrome -- Fiction; Autism -- Fiction; JUVENILE FICTION / Sports & Recreation / General; JUVENILE FICTION / Social Issues / Friendship; JUVENILE FICTION / Social Issues / General (see also headings under Family); Sports fiction